Psychological Well-Being in a Connected World: The Impact of Cybervictimization in Children’s and Young People’s Life in France - Audrin, Catherine; Blaya, Catherine (Frontiers in Psychology, 2020)
The Internet is at the heart of our children’s and adolescents’ way of life. Although it opens up many positive perspectives in terms of access to information, knowledge and communication, it also presents risks and potential negative experiences that can have severe consequences at the individual level. In this paper, we are interested in studying the link between cybervictimization, psychological well-being and social competence. More specifically, we want to study how children and adolescents’ anxiety, impulsivity, self-esteem and deviant behaviors may be related to cybervictimization. We collected data from 1,019 children and young people in France aged 9-17, in the context of the EU Kids online survey. Sampling was performed building a random-probability nationally representative sample of households with children using the Internet. Participants completed a questionnaire online by computer-assisted self-interviewing (CASI). Structural equation model reveals that 1) cybervictimization is related to lower well-being such as anxiety and low self-esteem as well as lower social competence like impulsivity and deviant behaviors, and that 2) all dimensions of (non)-wellbeing and social (in)competence are related to each other. Findings are discussed in the light of Agnew general strain theory and previous research findings on the consequences of cybervictimization